2006
DOI: 10.1590/s0100-54052006000300014
|View full text |Cite
|
Sign up to set email alerts
|

Reação de genotipos de feijoeiro comum a quatro raças de Fusarium oxysporum f. sp. phaseoli

Abstract: O objetivo do trabalho foi avaliar a resistência de 104 genótipos de feijoeiro comum, do Banco Ativo de Germoplasma do Instituto Agronômico de Campinas (BAG/IAC), a quatro raças fisiológicas de Fusarium oxysporum f. sp. Phaseoli em casa de vegetação para avaliação. Os sintomas da doença foram avaliadas nas plantas aos trinta dias após a inoculação, atribuindo-se notas que variavam de 0 (plantas sem sintomas) a 4 (plantas totalmente murchas e ou mortas). Plantas com notas médias de severidade até 2 foram consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 2 publications
0
8
0
2
Order By: Relevance
“…The existence of variability in the reaction to this pathogen was reported at several occasions (Salgado & Schwartz, 1993;Woo et al, 1996;Sala et al, 2006;Pereira et al, 2008). There are some reports of ge- netic control of resistance; the first was probably the study of Ribeiro & Hagedorn (1979), who identified the presence of only one gene with a dominant allele conferring resistance.…”
Section: Introductionmentioning
confidence: 97%
“…The existence of variability in the reaction to this pathogen was reported at several occasions (Salgado & Schwartz, 1993;Woo et al, 1996;Sala et al, 2006;Pereira et al, 2008). There are some reports of ge- netic control of resistance; the first was probably the study of Ribeiro & Hagedorn (1979), who identified the presence of only one gene with a dominant allele conferring resistance.…”
Section: Introductionmentioning
confidence: 97%
“…They include Bipolaris, which causes foliar diseases in rice (Celmer et al, 2007) and damage in the grass, Paspalum atratum cv. Pojuca (Anjos et al, 2004) and fungi of the genus Fusarium,, which is a disease agent in various hosts (Sala et al, 2006;Dias and Toledo, 1993), including castor bean. In general, the treatment with the biological product did not inhibit the growth of fungus species, including some, such as Fusarium (Silva et al, 2005), which are very important for castor bean, principally the AL Guarany 2002 cultivar (Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…Fusarium is a soil-inhabiting species and is often found on seeds, causing damage in various crops, such as basil (Reis et al, 2007), black pepper (Carnaúba et al, 2007), dry beans (Sala et al, 2006) and also castor bean, where it can cause severe damage (Silva, 2005). Alternaria is another fungus, associated with castor bean seeds, causing alternaria spot disease (Silva, 2005) and the fungus Macrophomina is responsible for one of the main diseases found in castor bean (stem or root rot) and various other crops via the seeds (Vanzolini et al, 2010).…”
mentioning
confidence: 99%
“…A resistência a múltiplas raças de F. oxysporum f. sp. phaseoli foi citada por Sala (2006), que avaliou 104 genótipos que apresentaram 33% de resistência às raças 1, 2, 3 e 4 do patógeno. Silva et al (2009) avaliaram 56 cultivares de feijoeiro quanto à resistência ao crestamento bacteriano e encontraram 37% dos genótipos com resistência ao patógeno.…”
Section: Adaptabilidade Estabilidade E Resistência a Patógenos Em Geunclassified